2021
DOI: 10.1111/ijcp.14880
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety, depression and post‐traumatic stress disorder symptoms in adolescents during the COVID‐19 outbreak and associated factors

Abstract: Coronavirus disease 2019 (COVID-19, also known as 2019-nCoV) was first detected in Wuhan, China, on 31 December 2019. The World Health Organization (WHO) announced COVID-19 as an international public health emergency and a pandemic. 1 While no appropriate treatment is available as yet, many countries are trying to manage the COVID-19 pandemic with combinations of social isolation strategies. The growing threat of the pandemic both in Turkey and around the world as well as social isolation and overload of me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 39 publications
(105 reference statements)
2
19
0
Order By: Relevance
“…Hou et al (2020) studied the prevalence of PTS in adolescents and children in China in the aftermath of COVID-19 and found a prevalence rate of 85.5%, while Zhang et al (2020) found a prevalence of 10.6% in a similar population. Selçuk et al (2021) has reported the prevalence rate of 28.5% of PTS in Turkey. The estimates provided by recent reviews are 48.0% (Ma et al, 2021) and 7-53.8% (Xiong et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hou et al (2020) studied the prevalence of PTS in adolescents and children in China in the aftermath of COVID-19 and found a prevalence rate of 85.5%, while Zhang et al (2020) found a prevalence of 10.6% in a similar population. Selçuk et al (2021) has reported the prevalence rate of 28.5% of PTS in Turkey. The estimates provided by recent reviews are 48.0% (Ma et al, 2021) and 7-53.8% (Xiong et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…A total of 11.5% of participants met the clinical criteria. Selçuk et al (2021) examined 447 adolescents during the COVID-19 outbreak on the moderate prevalence level of 28.5% of PTS in Turkey. This necessitates research focusing on children and adolescents.…”
Section: Introductionmentioning
confidence: 99%
“…In this present study, groups were allocated according to participants’ scores on the Beck Depression Inventory-II (BDI-II) [ 31 ] (young adults) and CDI [ 30 ] (adolescents). A growing body of literature supports the use of cut-off scores for these two instruments [ 32 34 ], and a considerable amount of literature has been conducted using depression as a categorical variable based on these exact BDI/CDI scores [ 35 , 36 ]. This also resulted in slightly different sample sizes/grouping relative to the Wante et al [ 19 ] study.…”
Section: Methodsmentioning
confidence: 99%
“…During the COVID-19 pandemic, a systematic review estimated that PTSD affects 48.0% of this population [ 4 ]. Some settings in this context have shown high rates of PTSD, such as Turkey (61.1%) [ 5 ] and Saudi Arabia (71.5%) [ 6 ].…”
Section: Introductionmentioning
confidence: 99%